Transition-metal doped, magnesium oxide-supported terbium oxides as catalysts for the oxidative coupling of methane. (15th September 2019) - Jones, Andrew S.; Alfonso, Nicolas; Hagelin-Weaver, Helena E.
Graphical abstract: The effect of transition metal dopants on TbO x / n -MgO was investigated in the oxidative coupling of methane. Low loadings (0.2 wt%) can significantly improve the performance over 1.0 wt% and undoped catalysts, likely due to incorporation into the TbO x lattice which increases the TbO x dispersion and the number of basic sites. Abstract: The effects of transition metal dopants on the catalytic properties of magnesia-supported terbium oxide catalysts in the oxidative coupling of methane were investigated. A few transition metals were included based on their oxidation states relative to Tb in TbO1.81 (where Tb is between Tb 3+ and Tb 4+ ). Ni and Fe were selected as low valence dopants (LVDs) and Zr and V were considered high valence dopants (HVDs) in the study. The effect of dopant concentration was also investigated, between 0.2 and 1.0 % by weight (wt%), since high loadings could result in segregation of the transition metal (TM) dopants, while low loadings may not yield observable effects. At the higher loading (1.0 wt%) it appears that the oxidation state relative to that of Tb is of minor importance, and the redox properties of the dopant have a larger impact. At this loading, the best performing catalysts were the Ni- and Zr-doped TbO x / n -MgO, while the selectivities of the Fe- and V-doped catalysts toward OCM products were very low, particularly at the lower temperatures (<600 °C). The facile redox reactions that allow Fe and V to easily change oxidation state are likely detrimental to the OCM reaction, particularly at higher concentrations where segregation of the transition metal oxide may occur at the surface. In contrast, at the lower loading (0.2 wt%) all doped catalysts performed better than the undoped TbO x / n -MgO. At this loading, it appears that the LVDs resulted in better performing OCM catalysts, as the Ni- and Fe-doped TbO x / n -MgO both had higher activities and selectivities compared with the Zr- and V-doped catalysts. The characterization data revealed that even at the low concentration of 0.2 wt%, the transition metals markedly alters the properties of the doped TbO x / n -MgO catalysts. For example, the number of basic sites was significantly increased by adding 0.2 wt% of Fe or Zr to the TbO x / n -MgO catalyst and this led to an improvement in the performance of the catalysts in the OCM reaction. The dopants also affected the oxidation state of Tb in the TbO x lattice as well as the dispersion of TbO x on the surface of the MgO. Both XPS and XRD data indicated that the TbO1.81, which was present on the surface of the fresh catalysts, in most cases was reduced to Tb2 O3 during reaction. However, there were no evident trends to indicate that LVDs promote, while HVDs suppress, surface reduction of the host oxide, i.e. TbO x . The lack of trends may in part be due to the presence of the MgO support, which results in a complex catalyst system. Nevertheless, the data revealed that even low loadings of a transition metal dopant can positively affect the activity and selectivity of a TbO x / n -MgO catalyst.